Proveniência e contexto digital : contribuições da ciência da informação - Arakaki, Felipe Augusto; Santos, Plácida Leopoldina Ventura Amorim da Costa (2021)
The objective of this article is to discuss the concept of provenance and highlight its importance in the digital environment, focusing on the perspective of Information Science. As methodological procedures, it was characterized by being a qualitative and exploratory research, from a literature review on the context of provenance in different domains. The article presents a discussion of the term provenance in several contexts, such as in Achival Science, Museology, Digital Preservation and Computing, highlighting its importance in the digital sphere. As discussed the relevance of provenance in different contexts, the need for more in-depth studies is highlighted, analyzing whether the instruments to represent provenance are adequate to guarantee the veracity and inalterability of the information. Thus, the discussions exposed in this article reveal possibilities in identifying metadata for each characteristic that the provenance may present, in addition to the feasibility of expansion to other contexts.
O objetivo deste artigo é discutir o conceito da proveniência e evidenciar sua importância no ambiente digital, focado na perspectiva da Ciência da Informação. Como procedimentos metodológicos, caracterizou-se por ser uma pesquisa qualitativa e exploratória, a partir de uma revisão de literatura sobre o contexto da proveniência em diferentes domínios. O artigo apresenta uma discussão do termo proveniência em diversos contextos, como na Arquivologia, Museologia, Preservação digital e Computação e destaca sua importância no âmbito digital. Conforme discutida a relevância da proveniência em diferentes contextos, destaca-se a necessidade de estudos mais aprofundados, se os instrumentos para representar a proveniência são adequados para garantir a veracidade e a inalterabilidade das informações. Dessa forma, as discussões expostas neste artigo revelam possibilidades em identificar metadados para cada característica que a proveniência possa apresentar, além da viabilidade de ampliação para outros contextos.
Keywords: Provenance; Digital environment; Context of provenance; Proveniência^lpt; Ambiente digital; Contexto da proveniência